MUI FATWA NO.83/2023: ITS IMPACT ON THE PROFITABILITY OF COMPANIES AFFILIATED WITH ISRAEL - Annisa Maulidiana; Trischa Relanda Putra (Fakultas Ekonomi dan Bisnis Islam Universitas Islam Negeri Raden Fatah Palembang, Indonesia, 2024)
The purpose of this study is to determine and analyze the differences in profitability as measured by ROA, ROE, and NPM between before and after the boycott according to MUI fatwa No. 83 of 2023. The population of this study were 9 companies affiliated with the state of Israel while the sample was taken with the criteria of companies affiliated with the state of Israel that have sharia shares. Based on these criteria, 6 companies were obtained. The analysis technique used is a different test using a paired sample t test but if the data is not normally distributed then the test is continued with the wilcoxon test. The results showed that there was a difference in profitability as measured by ROA between before and after the boycott where there was a decrease in ROA value after the boycott. There is a difference in profitability measured by ROE between before and after the boycott where there is a decrease in ROE value after the boycott. There is a difference in profitability measured by NPM between before and after the boycott where there is a decrease in NPM value after the boycott. The conclusion shows that there are differences in profitability measured by ROA, ROE and NPM between before and after the boycott where there is a decrease in ROA, ROE and NPM values after the boycott